A dual-functional nanoplatform based on NIR and green dual-emissive persistent luminescence nanoparticles for X-ray excited persistent luminescence imaging and photodynamic therapy. Issue 41 (13th October 2022) - Jiang, Huimin; Wang, Ruoping; Zhang, Qian; Song, Liang; Sun, Xia; Shi, Junpeng; Zhang, Yun
Abstract : X-ray-excited PLNPs with dual emission for in vivo X-rays repeatedly activated PerL imaging and tumor PDT are reported. Abstract : Persistent luminescence nanoparticles (PLNPs) possess advantages for high-sensitivity bioimaging and continuous photodynamic therapy (PDT) because they can emit persistent luminescence (PerL) after excitation ceases. However, PLNPs are limited to single-wavelength emission, which can only efficiently realize one of the functions of bioimaging or PDT. In addition, most PLNPs are excited by shallow tissue penetrating excitation light, which makes it difficult to achieve repeatable in vivo applications with high efficiency. Herein, X-ray-excited PLNPs (Zn3 Ga2 Ge2 O10 :Cr 3+, Mn 2+, ZGGCM) with dual emission for in vivo X-rays repeatedly activated PerL imaging and tumor PDT are reported for the first time. ZGGCM exhibits dual-emission peaks after X-ray excitation/re-excitation, located at 698 nm and 532 nm, respectively. Additionally, ZGGCM is modified with the photosensitizer rose bengal (RB) to construct a dual-functional nanoplatform based on PerL imaging and PDT. The results indicate that the PerL emission peak (698 nm) of Cr 3+ ions in ZGGCM possesses excellent near-infrared (NIR) PerL imaging performance, and the green PerL emission peak (532 nm) of Mn 2+ ions can activate RB effectively and generate reactive oxygen species (ROS), thereby causing a significant antitumor effect. This unique dual-functional nanoplatform is expected to further promote the application of PLNPs in the integration of efficient tumor diagnosis and treatment.